1996
DOI: 10.1063/1.116820
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency in dry etching of Si for wavelengths around 120 nm

Abstract: Microstructuring of Si with XeF2 can be optimized by increasing the contrast in choosing a wavelength with minimal nonselective etching. The efficiency of selective etching with optimal quality can be increased by factors of 100 and 500 by using wavelengths around 120 and 110 nm, respectively, in comparison to longer wavelengths around 200 nm. The high efficiency of typically 10 removed atoms per photon, the availability of optical materials for imaging and the potentially high spatial resolution at 120 nm com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The quantum efficiencies q 1 of removed Si atoms or GaAs units per photon incident in the cell have been determined from the number of photons cm −2 and the etched volume analogous to that of section 3.2 and are shown in figure 18. They are once more much larger than unity and reach values in the range of high efficiency between 60 to 80 for GaAs [24] and up to 100 for Si [21]. Since they exceed unity it is necessary per se that amplification processes as discussed in the Cu/Cl 2 case are present also here.…”
Section: Etching Efficiency Q 1 Amplification Q 2 and Pitch Sizementioning
confidence: 92%
See 1 more Smart Citation
“…The quantum efficiencies q 1 of removed Si atoms or GaAs units per photon incident in the cell have been determined from the number of photons cm −2 and the etched volume analogous to that of section 3.2 and are shown in figure 18. They are once more much larger than unity and reach values in the range of high efficiency between 60 to 80 for GaAs [24] and up to 100 for Si [21]. Since they exceed unity it is necessary per se that amplification processes as discussed in the Cu/Cl 2 case are present also here.…”
Section: Etching Efficiency Q 1 Amplification Q 2 and Pitch Sizementioning
confidence: 92%
“…In addition they have strong electronic transitions in the spectral range from 150 to 50 nm and it is expected that the reactivity can be enhanced further by stimulating these excited states with light. The reactions are induced on Cu plates [11][12][13][14][15] and films [16] and on single-crystalline Si(100) [17][18][19][20][21][22][23] and GaAs(100) [24][25][26][27] surfaces in order to cover relevant metallic and semiconductor systems. Due to the high reactivity of halogens it is necessary in a first step to separate the reaction of ground state atoms, which is independent from irradiation and therefore called dark reaction, from the light induced reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Ghosh and Bauld have found that electron acceptors (holes) in zeolites catalyze cyclo-addition reactions. 72 They report catalytic factors (products per hole) of 10 18 or higher! Because photo-assisted etching of Si is confined to the surface, and band bending would likely push the hole into the bulk, it is difficult to envision how such a process could lead to yields of 50, let alone 10 5 , as has been reported.…”
Section: Mechanisms For Photo-assisted Etchingmentioning
confidence: 99%
“…Etching of p-type Si induced by photo-generated carriers in a Cl 2 atmosphere was also obtained using a pulsed 308 nm XeCl excimer laser 10 and cw Ar þ and K þ lasers with various wavelengths. 11 Schwentner et al systematically investigated photo-induced etching of Cu [12][13][14][15] and GaAs 16 with Cl 2 , and etching of Si with XeF 2 [17][18][19] using synchrotron radiation in the vacuum UV (VUV) range. They found that photo-induced etching was strongly wavelength-dependent, with the maximum yield exhibited around 120 nm.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we summarize our new results on the wavelength dependence of light-induced dry etching of Si(100) derived from a systematic investigation of the selectivity [5] and the efficiency [6,7] of the reaction. Both aspects, a high selectivity and a large efficiency, are basic preconditions for an application in microstructuring.…”
Section: Introductionmentioning
confidence: 99%